GEOCHEMISTRY OF RARE ELEMENTS IN WATERS AND SEDIMENTS OF ALKALINE LAKES IN THE SASYKKUL DEPRESSION, EAST PAMIRS - Volkova N.I. (My University, 1998)
The saline lakes (Tuzkul, Chukurkul, Sasykkul Lakes) of the Sasykkul depression located in the semidesert part of the Pamirs provide a prominent example of the evaporative concentration of alkaline waters in a closed basin under arid climate conditions. Chemical evolution of the lake waters has resulted in the development of residual Na–Cl–CO3–SO4 and Na–Cl–CO3 brines. The contents of a number of rare elements were determined in waters and sediments of the Sasykkul depression lakes. Speciation modelling suggests that the main aqueous species of Ag are chloride complexes, Cu, Pb, Zn, Mn are carbonate complexes, Be, Bi, Nb are hydroxocomplexes, Mo, W, As, V are oxyanions. It was established that the salt lake sediments are significantly enriched in B, Ba, Mo, W, U, Th. High contents of trace elements are considered to be due to chemical weathering of rocks within the catchment basin, significant contribution from thermal springs derived from the residual fluids associated with acid igneous and volcanic rocks, and following evapoconcentration in a closed basin. The processes of evaporative concentration, solution complexation, chemical precipitation, and water-sediment interaction lead to the partitioning of trace metals in the salt sediments.